2010
DOI: 10.1002/fuce.200900139
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microwave‐Assisted Solvothermal Synthesis of Methanol Tolerant Pt–Pd–Co Nanoalloy Electrocatalysts

Abstract: We report here a microwave‐assisted solvothermal (MW‐ST) method to synthesise carbon‐supported multimetallic nanostructured alloys of Pt, Pd and Co with high crystallinity and homogeneity for electrocatalytic application in fuel cells. Multimetallic nanoalloy electrocatalysts have been synthesised by a one‐pot, rapid MW‐ST method within 15 min at <300 °C without any post‐annealing in reducing gas atmospheres. For a comparison, same multimetallic alloys were also synthesised by heat treatment of co‐precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…There are few works in the literature that report the performance under realistic conditions in a DMFC of Pd‐based cathodes. The performance obtained in this work using a total Pt loading in the cell as low as 0.56 mg cm −2 (0.5 mg cm −2 at the anode and 0.06 mg cm −2 at the cathode) are comparable to those obtained when using a similar composition but a Pt loading of 2.5 mg cm −2 29…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…There are few works in the literature that report the performance under realistic conditions in a DMFC of Pd‐based cathodes. The performance obtained in this work using a total Pt loading in the cell as low as 0.56 mg cm −2 (0.5 mg cm −2 at the anode and 0.06 mg cm −2 at the cathode) are comparable to those obtained when using a similar composition but a Pt loading of 2.5 mg cm −2 29…”
Section: Resultssupporting
confidence: 74%
“…The performance obtained in this work using a total Pt loading in the cell as low as 0.56 mg cm À2 (0.5 mg cm À2 at the anode and 0.06 mg cm À2 at the cathode) are comparable to those obtained when using a similar composition but a Pt loading of 2.5 mg cm À2 . [29] Conclusion Pd-based catalysts usually present lower catalytic activity than their Pt-based counterparts in DMFCs. The use of a composite Pd-Pt catalyst with a very low Pt content (5 wt.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave method is highly advantageous over the conventional borohydride reduction methods; the reaction mechanism of microwave methodology is described elsewhere [28,30]. The MWAS method provides a uniform nucleation environment and offers highly crystalline monodispersed metal nanoparticles.…”
Section: Significance Of the Microwave Synthetic Methodsmentioning
confidence: 99%
“…The microwave-assisted solvothermal synthesis (MWAS) is an attractive synthetic strategy for the preparation of nanosized catalysts [26][27][28]. It is faster, cleaner, simpler than the conventional borohydride reduction methods [26][27][28]. For example, Manthiram and co-workers [28] recently reported that alloys, synthesised by the MWAS strategy, enhanced electrocatalytic reduction of oxygen compared to their counterparts synthesised by the conventional borohydride reduction method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation